Deformations of plane curves and Jacobian syzygies. Issue 3 (29th December 2019) - Dimca, Alexandru; Sticlaru, Gabriel
Abstract: We relate the equianalytic and the equisingular deformations of a reduced complex plane curve to the Jacobian syzygies of its defining equation. Several examples and conjectures involving rational cuspidal curves are discussed.